Hospital-based patient navigation programmes for patients who experience injury-related trauma and their caregivers: a scoping review protocol. Issue 4 (22nd April 2022) - Doucet, Shelley; Luke, Alison; Anthonisen, Grailing; Witherspoon, Richelle; MacNeill, A Luke; MacNeill, Lillian; Kelly, Katherine J; Fearon, Taylor
Abstract : Introduction: Patients who experience injury-related trauma tend to have complex care needs and often require support from many different care providers. Many patients experience gaps in care while in the hospital and during transitions in care. Providing access to integrated care can improve outcomes for these patients. Patient navigation is one approach to improving the integration of care and proactively supporting patients and their caregivers as they navigate the healthcare system. The objective of this scoping review is to map the literature on the characteristics and impact of hospital-based patient navigation programmes that support patients who experience injury-related trauma and their caregivers. Methods and analysis: This review will be conducted in accordance with Joanna Briggs Institute methodology for scoping reviews. The review will include primary research studies, unpublished studies and evaluation reports related to patient navigation programmes for injury-related trauma in hospital settings. The databases to be searched will include CINAHL (EBSCO), EMBASE (Elsevier), ProQuest Nursing & Allied Health, PsycINFO (EBSCO) and MEDLINE (Ovid). Two independent reviewers will screen articles for relevance against the inclusion criteria. Results will be presented in a Preferred Reporting Items for Systematic Reviews and Meta-analyses for Scoping Reviews (PRISMA-ScR) flow diagram and follow the PRISMA-ScR checklist. The extracted data will be presented both tabularly and narratively. Ethics and dissemination: Ethics approval is not required, as the scoping review will synthesise information from publicly available material. To disseminate the findings of this review, the authors will submit the results for publication in a medical or health sciences journal, present at relevant conferences and use other knowledge translation strategies to reach diverse stakeholders (eg, host webinars, share infographics).